The The influence of esg performance on stock price volatility in Indonesia - Sidharta, Kevin; Kim, Sung Suk (Enrichment : Journal of Management, 2024)
This study investigates the influence of Environmental, Social, and Governance (ESG) performance on stock price volatility in the Indonesian stock market. The research focuses on four main points. First, the stock market provides potential capital growth through dividends and capital gains, with capital gains offering higher returns but also carrying the risk of losses if stock prices decline. Second, stock price volatility can be high during economic crises, such as the COVID-19 pandemic, which has the potential to trigger significant downturns (market crashes). Third, internal factors of companies such as size, profitability, and strategy influence the stability of stock price volatility, especially during crises. Fourth, ESG disclosure is increasingly important for investors seeking sustainable practices and effective risk management. Companies with high ESG scores tend to send positive signals to investors, reducing uncertainty and increasing confidence. The study's findings suggest that ESG performance has the potential to reduce stock price volatility, especially in non-crisis conditions. This research provides valuable insights for regulators, investors, and companies to understand how ESG affect the dynamics of the Indonesian stock market